2013
DOI: 10.1002/jso.23473
|View full text |Cite
|
Sign up to set email alerts
|

Local recurrence after radical nephrectomy for kidney cancer: management and prediction of outcomes. a multi‐institutional study

Abstract: Local recurrence after radical nephrectomy is associated with poor prognosis. The time to recurrence and the completeness of the surgical treatment are major prognostic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 24 publications
7
29
0
1
Order By: Relevance
“…Consistent with previous reports, the median time to development of RFR after RN in the present cohort was 1.4 years. This relatively short median time to development of RFR after RN is consistent with previous studies, in which median time to recurrence ranged from 1.1 to 3.3 years . The majority of these lesions were discovered on standard surveillance imaging.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with previous reports, the median time to development of RFR after RN in the present cohort was 1.4 years. This relatively short median time to development of RFR after RN is consistent with previous studies, in which median time to recurrence ranged from 1.1 to 3.3 years . The majority of these lesions were discovered on standard surveillance imaging.…”
Section: Discussionsupporting
confidence: 90%
“…Among this cohort, 33 patients presented with iRFR, while 30 patients presented with RFR in the setting of synchronous metastatic disease. The finding that nearly half of patients presented with RFR and synchronous metastases is similar to that reported by Bruno et al The present series of RFRs differed from several of the previously reported case series and retrospective cohorts in that ipsilateral adrenal recurrences were excluded from the study cohort, such that RFR describes only radiographical recurrences to the renal fossa and regional lymph nodes .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…They noted, on univariate analysis only, that time to recurrence and surgical intervention remained independent predictive factors for cancer specific mortality. 26 However, this study included a significant number of patients (30%) with concomitant distant metastases at time of RPR. In contrast, all cases in our study were performed at a single institution, and no patients had detectable distant metastases at the time of RPR surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Patients undergoing surgery for symptomatic recurrences have a higher rate of incomplete resection of recurrence, positive surgical margins and worse survival compared to surgery without symptoms. [41][42][43] Extensive tumour recurrence reduces the possibility of complete surgical resection, which is standard therapy for patients with local recurrence or resectable solitary metastasis. Furthermore, an early diagnosis of metastatic disease relapse may enhance efficacy of systemic therapy or allow for metastasectomy if the tumour burden is low.…”
Section: Kassouf Et Al Non-metastatic Rcc Followupmentioning
confidence: 99%